PRELIMINARY STUDY OF COMMON PB OF UHP METAMORPHIC ROCKS FROM CCSD (100 TO 2000M): EVIDENCE FOR DECOUPLING WITHIN SUBDUCTING CONTINENTAL CRUST - Dong F.; Li S.G.; Liu Y.C.; Li Q.L.; Chen F.K. (My University, 2006)
This paper reports common Pb isotope data of omphacite in eclogite and feldspar in gneiss from the Chinese Continental Scientific Drilling (CCSD) (100 ~ 2000m). The radiogenic Pb of samples from the upper section (0 ~ 800m) in drilling core is moderately high with small variations (206Ph/204Pb = 16.81 ~ 17.29, 207Pb/204Pb = 15.37 ~ 15.45, 206Ph/204Pb = 37.20 ~ 37.66), indicating either high U/Pb and Th/Pb or high initial Pb isotope ratios of their protoliths. The radiogenic Pb of samples from the middle section (800 ~ 1600m) in the drilling core, where ductile shear zones are developed, begins to drop with larger variations (206Ph/204Pb = 16.26 ~ 16.72, 207Pb/204Pb = 15.27 ~ 15.38, 206Pb/204Pb = 36.73 ~ 37.40). The radiogenic Pb of samples from the lower section (1600 ~ 2000m) is moderately low with small variations (206Pb/204Pb = 16.05 ~ 16.46, 207Pb/204 Pb = 15.22 ~ 15.29, 208Pb/204 Pb = 36.68 ~ 37.48) indicating either low U/Pb and Th/Pb or low initial Pb isotope ratios of their protoliths. Comparison between the observed Pb isotopic data and modeling of Pb isotope evolution suggests that the common Pb difference between the upper and lower sections of the drilling core partly inherited from the initial Pb isotope difference between their protoliths, and partly caused by difference μ values of their protoliths. Combined with oxygen isotope data, we interpret the upper and lower sections are two different slabs derived from subducting upper curst and middle crust, respectively. The former is the decoupled upper crust from the subducting continental lithosphere. The detachment between the upper slab and subducting continental lithosphere might have occurred during the continental subduction time, and then the upper slab was uplifted to a shallow depth along the detachment surface by thrust. The lower slab may be a decoupled middle crust, which was detached from the subducting continental lithosphere latterly and was uplifted to a shallower depth below the upper slab. The lowest δ18O value (Xiao et al., 2006) in ductile shear zones of the middle section (800 ~ 1600m) suggests that the detachment surface might have developed along an ancient fault zone, which was a channel of cold meteoric water activity in late Proterozoic.
Keywords: CHINESE CONTINENTAL SCIENTIFIC DRILLING PROJECT (CCSD); COMMON LEAD; DABIE-SULU; UHP METAMORPHIC ROCKS; Докембрий::Протерозой; Precambrian::Proterozoic